Integrated gene network analysis and experimental validation identify key hub genes in potato response to Potato Virus Y infection - Roya Karimipour; Davoud Koolivand; Abozar Ghorbani; Masoud Naderpour; Mahsa Rostami (PLoS ONE, 2025)
Potato (Solanum tuberosum) is a staple food crop that supports global food security, ranking as the world’s third most important food crop after rice and wheat in terms of human consumption, and it is threatened by Potato virus Y (PVY), which causes severe yield losses. This study integrates bioinformatics analysis and experimental approaches to elucidate molecular defense mechanisms against PVY infection. Using transcriptomic data from PVY-infected potato plants, we constructed protein-protein interaction (PPI) networks and identified hub genes central to defense responses. The qPCR validation showed that three hub genes (NAD1, NAD2, NAD3) were upregulated in resistant Sante plants but downregulated in susceptible Agria. Among these, NAD2 showed a striking 5.58-fold increase in Sante, highlighting its critical role in stress signaling and antiviral defense. Network analysis revealed interactions with microRNAs (miRNAs), including stu-miR8015-5p and stu-miR396-5p, suggesting complex regulatory networks. Codon usage bias analysis highlighted adaptive codon preferences optimized for translational efficiency, supporting potential strategies like codon deoptimization to impair viral fitness. Promoter motif analysis identified stress-responsive cis-regulatory elements linked to abscisic acid signaling, critical for antiviral responses. This comprehensive study establishes a framework for targeting hub genes and miRNAs to engineer PVY-resistant cultivars, thereby offering a sustainable solution.